Treatment of Unspecific Back Pain in Children and Adolescents: Results of an Evidence-Based Interdisciplinary Guideline - Frosch, Michael; Leinwather, Stina; Bielack, Stefan; Bloedt, Susanne; Dirksen, Uta; Dobe, Michael; Geiger, Florian; Haefner, Renate; Hoefel, Lea; Huebner-Moehler, Bettina; Von Kalle, Thekla; Lawrenz, Burkhard; et al. (Children, 2022)
Using a structured approach and expert consensus, we developed an evidence-based guideline on the treatment and prevention of non-specific back pain in children and adolescents. A comprehensive and systematic literature search identified relevant guidelines and studies. Based on the findings of this literature search, recommendations on treatment and prevention were formulated and voted on by experts in a structured consensus-building process. Physical therapy (particularly physical activity) and psychotherapy (particularly cognitive behavioral therapy) are recommended for treating pediatric non-specific back pain. Intensive interdisciplinary treatment programs should be provided for chronic and severe pain. Drug therapy should not be applied in children and adolescents. Further research on non-specific back pain in childhood and adolescence is strongly needed to reduce the imbalance between the high burden of non-specific back pain in childhood and adolescence and the low research activity in this field.
CRIS-Team Scopus Importer:2022-04-08
Keywords: adolescents; back pain; children; evidence-based; guideline; prevention; treatment